Distribution of Vaginal and Gut Microbiome in Advanced Maternal Age - Huang, Yuxin; Li, Dianjie; Cai, Wei; Zhu, Honglei; Shane, Mc Intyre; Liao, Can; Pan, Shilei (Frontiers in Cellular and Infection Microbiology, 2022)
The distribution of microbiome in women with advanced maternal age (AMA) is poorly understood. To gain insight into this, the vaginal and gut microbiota of 62 women were sampled and sequenced using the 16s rRNA technique. These women were divided into three groups, which included the AMA (age ≥ 35 years, n = 13) group, non-advanced maternal age (NMA) (age < 35 years, n = 38) group and control group (non-pregnant healthy women, age >35 years, n = 11). We found that the alpha diversity of vaginal microbiota in the AMA group significantly increased. But the beta diversity significantly decreased in the AMA group compared with the control group. The distributions of microbiota were significantly different among AMA, NMA, and control groups. Vaginal and gut microbiota in women with AMA were noticeably different from the NMA and non-pregnant women, and this phenomenon is probably related to the increased risk of complications in women with AMA.